2011
DOI: 10.1021/ja111517e
|View full text |Cite
|
Sign up to set email alerts
|

Self-Regulating Enzyme−Nanotube Ensemble Films and Their Application as Flexible Electrodes for Biofuel Cells

Abstract: Nanostructured carbons have been widely used for fabricating enzyme-modified electrodes due to their large specific surface area. However, because they are random aggregates of particular or tubular nanocarbons, the postmodification of enzymes to their intrananospace is generally hard to control. Here, we describe a free-standing film of carbon nanotube forest (CNTF) that can form a hybrid ensemble with enzymes through liquid-induced shrinkage. This provides in situ regulation of its intrananospace (inter-CNT … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
135
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 218 publications
(136 citation statements)
references
References 30 publications
1
135
0
Order By: Relevance
“…One attractive study has been reported by Miyake et al for fructose oxidation. [311] A CNT forest was grown in the presence of an enzyme solution, and the network was shown to shrink to a near-hexagonal closepacked structure, with the intra-nanospace regulated by the size of the enzymes. For fructose oxidation, a current of up to 16 mA cm À2 was reached.…”
Section: Enzyme Quantification In 3d Networkmentioning
confidence: 99%
“…One attractive study has been reported by Miyake et al for fructose oxidation. [311] A CNT forest was grown in the presence of an enzyme solution, and the network was shown to shrink to a near-hexagonal closepacked structure, with the intra-nanospace regulated by the size of the enzymes. For fructose oxidation, a current of up to 16 mA cm À2 was reached.…”
Section: Enzyme Quantification In 3d Networkmentioning
confidence: 99%
“…For example, nanostructured carbons, such as carbon nanotubes [3][4][5][6][7] and carbon blacks, [8][9][10] and mesoporous carbons, such as carbon cryogel [11][12][13][14][15] and carbon aerogel, 16,17 have been investigated for use as enzyme electrode scaffolds. Carbon nanotubes and carbon blacks aggregate and create mesospaces suitable for enzymatic reactions.…”
Section: Introductionmentioning
confidence: 99%
“…As to the development of the anode of the ASA2P fuel cell, the methods of fabricating the enzyme electrodes for amperometric biosensors and other biofuel cells can be applied, [9][10][11][12] in which the use of conducting polymers is helpful. The authors reported in a previous paper 13 that the film composed of polyaniline (PANI) and poly(acrylic acid) (PAA) showed both conductivity and electrochemical activity.…”
Section: Introductionmentioning
confidence: 99%